Influence of Environmental Factors with Clinical Signs and Symptoms in the Management of Dry Eye Disease - Muñoz-Villegas P; García-Sánchez G; Jauregui-Franco RO; Quirarte-Justo S; Sánchez-Ríos A; Olvera-Montaño O (Clinical Ophthalmology, 2024)
Patricia Muñoz-Villegas,1,2 Gisela García-Sánchez,1 Ricardo O Jauregui-Franco,1 Sebastian Quirarte-Justo,1 Alejandra Sánchez-Ríos,1 Oscar Olvera-Montaño1 1Regional Medical Affairs Department, Laboratorios Sophia, S.A. de C.V., Zapopan, Jalisco, Mexico; 2Centro de Investigación en Matemáticas, A.C., Unidad Aguascalientes (CIMAT), Aguascalientes, Aguascalientes, MexicoCorrespondence: Patricia Muñoz-Villegas, Laboratorios Sophia, S.A. de C.V., Paseo del Norte 5255, Technology Park, Zapopan, Jalisco, 45010, México, Tel +52 33 3001 4200, Email patricia.munoz@sophia.com.mxBackground: This research aims to investigate the influence of environmental factors on the treatment efficacy of ocular lubricants in patients from urban areas with dry eye disease (DED).Methods: A phase IV clinical trial, which included 173 patients from major cities in Mexico, was randomly assigned to use ocular lubricants four times a day for 30 days. Ocular Surface Disease Index (OSDI), noninvasive tear film break-up time (NIBUT), ocular staining, and conjunctival hyperemia (CH) among other factors like weather, and air pollution as covariates were analysed.Results: After 30 days, OSDI score decreased by 14.8 points (p< 0.001), and NIBUT increased by 2.9 seconds (p< 0.001), with longer values observed in patients recruited in autumn and winter (additional 1.8 seconds, p< 0.05) compared to those recruited in spring. Patients living in cities with cooler weather and high humidity, but low air quality had higher OSDI and conjunctival stain scores of up to 4.4 and 0.3 points, respectively, as compared to those living in cities with similar pollution and humidity levels but with higher temperatures (p-values= 0.019 and 0.050). Patients with moderate CH had an increase of up to 0.8 points in their corneal stain score (p< 0.010). We also found that ozone levels were related to the predicted changes in OSDI and NIBUT.Conclusion: This study demonstrated the impact of environmental factors on the signs and symptoms of DED and suggests that patients residing in cities with inadequately controlled air pollution can benefit from using ocular lubricants to alleviate their symptoms.Trial Registration: Trial is registered at clinicaltrials.gov (NCT04702776).Keywords: Dry eye disease, dry eye symptoms, dry eye signs, environmental factors, ocular lubricants